Rest-activity circadian rhythm in breast cancer survivors at 5 years after the primary diagnosis. (3rd August 2019) - Roveda, Eliana; Bruno, Eleonora; Galasso, Letizia; Mulè, Antonino; Castelli, Lucia; Villarini, Anna; Caumo, Andrea; Esposito, Fabio; Montaruli, Angela; Pasanisi, Patrizia
ABSTRACT: Rest-activity circadian rhythm (RAR) is a marker of the circadian timing system. Particular attention has been given to RAR characteristics in cancer diseases. Specifically, alterations of RAR parameters have been found, at different stages of clinical pathway, in breast cancer (BC) patients. No studies to date have analyzed RAR alterations in breast cancer survivors several years after the diagnosis. The aim of this study was to determine RAR by actigraphy in a population of BC survivors at 5 years after the primary diagnosis, and to compare their RAR characteristics with healthy controls. The study sample was 28 women: 15 BC survivors at 5 years from the primary diagnosis (BC-group) and 13 healthy controls (Ctrl-group), matched for age and body mass index. All participants have been monitored for 7 days by actigraphy to evaluate RAR. A statistically significant circadian rhythm (T = 24) was found in all 28 subjects ( p < .001). The group analysis revealed a significant RAR both in BC- and Ctrl-group ( p < .001). The acrophase was not different between the BC- and Ctrl-group (15:09 vs . 15:01 hr:min in BC- and Ctrl-group, respectively). In contrast, the MESOR (Midline Estimating Statistic of Rhythm) and the amplitude were lower in the BC-group with respect to the Ctrl-group. Indeed, the MESOR was 192.0 vs . 276.4 activity counts in BC- and Ctrl-group, respectively ( p < .001), while the amplitude was 167.0 vs . 222.6 activity counts in BC- and Ctrl-group, respectively ( p < .001). These results provide the first experimental evidence of alterations in RAR parameters in BC survivors at 5 years after the primary diagnosis. Larger studies with a prospective design are needed to assess the role of RAR in the quality of life and prognosis in BC survivors.